К анатомическому обоснованию механизма неутомимости птиц при их отдыхе и наземной локомоции - Аметов, Закир (Вестник зоологии, 1970)
The comparative-anatomical and functional analysis is given of a series of pelvis limb muscles in representatives of some closely related and remote groups of birds with similar and different type of locomotion. It was found that the caudal part of iliotibialis muscles and additional part of semitendinosus muscle play probably a leading part in Passer and Galli ability to have a rest on a branch or roost without a special expenditures of muscle energy. Anseres, which cannot have a rest on a branch, have no caudal part of iliotibialis muscle and additional part of semitendinosus muscle. The presence of the additional part of caudo-femoralis muscle in both Galli and Anseres testifies to the similarity of movements in these birds when padding the soil (Galli) and swimming (Anseres). Passers, which have no additional part of the caudo-femoralis muscle, are not able to make such movements.